Data Interpolating Empirical Orthogonal Functions (DINEOF): a tool for geophysical data analyses - ALVERA-AZCÁRATE, A.; BARTH, A.; SIRJACOBS, D.; LENARTZ, F.; BECKERS, J. M. (Mediterranean Marine Science, 2011)
no abstract